Intimacy for Older Adults in Long-term Care: A Need, a Right, a Privilege - or a Kind of Care? - Schouten, V; Henrickson, M; Cook, Catherine; McDonald, S; Atefi, N (BMJ, 2022)
Background To investigate attitudes of staff, residents and family members in long-term care towards sex and intimacy among older adults, specifically the extent to which they conceptualise sex and intimacy as a need, a right, a privilege or as a component of overall well-being. Methods The present study was a part of a two-arm mixed-methods cross-sectional study using a concurrent triangulation design. A validated survey tool was developed; 433 staff surveys were collected from 35 facilities across the country. Interviews were conducted with 75 staff, residents and family members. Results It was common for staff, residents and family members to talk about intimacy and sexuality in terms of rights and needs. As well as using the language of needs and rights, it was common for participants to use terms related to well-being, such as fun, happiness or being miserable. One participant in particular (a staff member) described receiving intimate touch as a ‘kind of care’—a particularly useful way of framing the conversation. Conclusion While staff, residents and family frequently used the familiar language of needs and rights to discuss access to intimate touch, they also used the language of well-being and care. Reframing the conversation in this way serves a useful purpose: it shifts the focus from simply meeting minimum obligations to a salutogenic approach—one that focuses on caring for the whole person in order to improve overall well-being and quality of life.